Pd/In-based catalysts for nitrate catalytic removal from water: synthesis designs aiming for better N2 selectivity - Sacco, Nicolás Alejandro (2023)
Pollution of surface and groundwater by nitrates is one of the major worldwide environmental problems. Pd/In-based catalysts were preparedby the wet impregnation method using Al2O3, SiO2, and TiO2 as supports. The influence of the synthesis procedure in the searchfor catalysts with high selectivity to N2 was studied. The materials were characterized by X-ray fluorescence and scanning electronmicroscopy-EDS analysis and evaluated in the catalytic nitrate removal from water employing a batch reactor. The catalytic performancewas influenced by the support used in the synthesis, obtaining the following order of better nitrate removal: Al2O3.TiO2.SiO2. Moreover,the selectivity to N2 is affected by the support used, being Al2O3-based catalyst being the most selective to N2 and TiO2-based catalysts theless one due to the strong metal?support interaction. On the other hand, the order of the synthesis stages affects the nitrate removal efficiencyand the selectivity, being the catalysts in which In was added after Pd with intermediate calcination and reduction stages and aposterior reduction, the most selective to N2 (94.4% at 90% of nitrate conversion).